(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article gives an attempt attempt to prove the necessity of using a systematic approach to determining the structure of local payments in Ukraine, as this structure has not yet formed during the years of independence of our state. It is necessary to review the existing approaches to the determination of local taxes and charges, combining them in local charges. It is necessary to review the existing approaches to the determination of local taxes and fees in the in the Ukrainian economic literature, combining them in the system of local payments. The analysis of the development of local payments in historical terms, and the experience of the USA show the necessity of inclusion such component as income from self-taxation of residents of local communities to the system of local payments. Investigation of local payments system in some EU countries also suggests the need for expansion of the existing system of local payments in Ukraine. Such components as income from philanthropy, income from sponsorship, 1% personal income tax for local community, voluntary-compulsory contributions of local communities residents to the development of local education and health care, contributions of the citizens to conduct counterterrorist operation should be included in this system. The proposed expansion of the structure of local payments will stabilize this structure, regardless of the changes in government.